Characteristics and Outcomes of Heart Failure Outpatients with Improvement in Ejection Fraction in Qatar - Rasha Kaddoura; Jassim Zaheen Shah; Mohamed Izham Mohamed Ibrahim; Rajvir Singh; Ammar Chapra; Haisam Alsadi; Maha Al Amri; Tahseen Hamamyh; Manar Fallouh; Farras Elasad; Mohamed Salah Abdelghani; Sumaya Alsaadi Alyafei; et al. (Heart Views)
Introduction: Heart failure with reduced ejection fraction (HFrEF) in Qatar has not been well characterized in the outpatient setting. Objective: To describe the characteristics of patients with HFrEF who had improvement in their left ventricular ejection fraction (LVEF) and independent predictors of improvement. Methods: This retrospective cohort study conducted at the advanced heart failure (HF) clinic in Qatar recruited patients who visited the clinic between January 2017 and December 2018. Adult patients were eligible if they were diagnosed with HFrEF (LVEF < 40%) and had two echocardiograms separated by at least 6 months. Results: Of 582 eligible patients, 161 (27.7%) had improved LVEF. They were younger (53.4 vs. 57.3 years, P = 0.002) and had shorter duration of HF diagnosis (4.3 vs. 5.6 years, P = 0.001). They experienced lower rates of all-cause hospitalization (20.5% vs. 38.0%, P = 0.001) and emergency department visits (25.5% vs. 35.9%, P = 0.001), without a difference in hospital mortality rate, than those without LVEF improvement. Decreased odds ratio of improved LVEF was associated with per year increase in age (adjusted odds ratio [aOR]: 0.98, 95% confidence interval [CI]: 0.97–0.99, P = 0.03), presence of left bundle branch block (aOR: 0.40, 95% CI: 0.20–0.80, P = 0.001), duration of HF diagnosis (aOR: 0.85, 95% CI: 0.78–0.94, P = 0.001), and ischemic HF etiology (aOR: 0.50, 95% CI: 0.30–0.77, P = 0.001; compared with dilated etiology). Beta-blocker therapy was associated with higher odds of LVEF improvement (aOR: 2.65, 95% CI: 1.02–6.88, P = 0.001). Conclusion: Patients with HFrEF with improved LVEF were younger, had a nonischemic cardiomyopathy, and had significantly fewer hospitalizations and emergency department visits.